Relational and cognitive dynamics in collaborative learning: lessons from Pancasila integration in Indonesia - Asri Asri; Badaruddin Badaruddin; Muhammad Idris (Frontiers in Education)
This study explores how interaction quality in collaborative learning relates to student outcomes and satisfaction in Indonesian high schools, with a focus on cognitive, metacognitive, and relational group activities. Conducted with 117 students across 23 groups in Takalar, Indonesia, the research employed a newly developed and validated questionnaire tailored to capture the nuances of collaborative learning and the integration of Pancasila values. The results demonstrate that high-quality interaction—especially a positive group climate, active participation, and supportive communication—significantly correlates with improved learning outcomes and satisfaction. Furthermore, individual perspective-taking skills were positively linked to interaction quality, while beliefs about learning showed no significant correlation. At the group level, a strong sense of community was associated with better collaboration and higher satisfaction. This study contributes uniquely by embedding Pancasila values, such as gotong royong (mutual cooperation) and social justice, into the assessment of collaborative learning in post-COVID educational settings. While the cross-sectional design and reliance on self-reports limit causal interpretation, the findings offer valuable insights for educators in designing inclusive and culturally grounded collaborative learning environments. The study highlights the importance of relational dimensions and cultural values in enhancing interaction quality and educational resilience in the digital era, especially in Southeast Asian educational contexts. These findings provide a meaningful basis for integrating national philosophical values into pedagogical frameworks that promote both academic and social–emotional development among students.